Aktualisasi Materi dan Refleksi Pembelajaran dalam Pra Amaliyah Tadris: Studi Penguatan Kompetensi Pedagogik Mahasiswa Pascasarjana Pendidikan Agama Islam - Shinta Kurnia Ilahi, Dewi; Begi Muhammad; Indra Dwi Irmawati Setiawan Putri; Suhud al Fausi; Moh Imam Bukhori; Moh Hasan Firghol Muttaqien (Kartika: Jurnal Studi Keislaman, 2025)
The Pra Amaliyah Tadris activity is a strategic initiative for preparing prospective lecturers in Islamic Religious Education (PAI), emphasizing content mastery and a culture of reflection. This study aims to analyze the instructional content delivered and to evaluate participants' responses and feedback from supervising lecturers. Employing a qualitative approach with a case study method, the research focused on the implementation of Pra Amaliyah Tadris by postgraduate students of PAI at UNZAH. The findings indicate that the topic “Forgetting and Transfer in Learning,” presented through a participatory approach, effectively enhanced student engagement and metacognitive awareness. Meanwhile, lecturers provided feedback regarding the need for improved time management and material visualization. The study recommends strengthening academic supervision and developing evaluation standards based on participant responses to improve the program's effectiveness